PENGARUH REKRUTMEN DAN SELEKSI TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PAREPARE - Haryadi, Mutiara (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
The objective of this research is to describe and analyze the influence of recruitment and selection on employee performance of PDAM Kota Parepare.The data collection techniques used are observation and questionnaires.The object of this research is the Regional Drinking Water Company (PDAM) of Parepare City with a total population of 112 respondents.Based on the results of the research that has been done, it shows that: 1) recruitment has a positive and significant effect on employee performance at PDAM Kota Parepare.2) selection has a positive and significant effect on employee performance at PDAM Kota Parepare.3) recruitment and selection simultaneously affect employee performance at PDAM Kota Parepare.